The authority concerned with administrative licenses : A comparative study - Mohammed, ُُEnas; Mohammed, Rasha (Journal of Legal Sciences, 2022)
The administrative authority (the administration) exercises its activity or work through two forms of business. This administrative act in which the intention of the administrative authority (the administration) is to have a specific legal effect. The risk, and whether the administration is restricted or discretionary in exercising its authority in the licensing area, it must not deviate from the legitimacy framework.Accordingly, and to be informed of this, we divide our study into three sections, in the first of which we deal with the definition of administrative licenses, and in the second of it we explain the competent authority for administrative licenses in comparative law, and in the third we highlight the authority concerned with administrative licenses in Iraqi law, and then conclude our study with a set of conclusions and recommendations.